THE PRINCIPLES OF TEACHING RECEPTIVE SKILLS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article discusses the principles of teaching receptive skills in foreign language teaching. According to it, it includes information about reading and listening comprehension skills and their basic techniques and examples of them.